Loss-of-function N178T variant of the human P2Y4 receptor is associated with decreased severity of coronary artery disease and improved glucose homeostasis - Horckmans, Michael; Diaz Villamil, Esteban; Verdier, Céline; Laurell, Henrik; Ruidavets, Jean-Bernard; De Roeck, Lucas; Combes, Guillaume; Martinez, Laurent O.; Communi, Didier (Frontiers in Pharmacology, 2022)
Human P2Y4 is a UTP receptor, while in mice it is activated by both ATP and UTP. P2Y4 knockout (KO) mice are protected against myocardial infarction and characterized by increased adiponectin secretion by adipocytes, and decreased cardiac inflammation and permeability under ischemic conditions. The relevance of these data has, however, not been explored to date in humans. In a population study comprising 50 patients with coronary artery disease (CAD) and 50 age-matched control individuals, we analyzed P2RY4 mutations and their potential association with CAD severity and fasting plasma parameters. Among the mutations identified, we focused our attention on a coding region polymorphism (rs3745601) that results in replacement of the asparagine at residue 178 with threonine (N178T) located in the second extracellular loop of the P2Y4 receptor. The N178T variant is a loss-of-function mutation of the human P2Y4 receptor and is encountered less frequently in coronary patients than in control individuals. In coronary patients, carriers of the N178T variant had significantly reduced jeopardy and Gensini cardiac severity scores, as well as lower resting heart rates and plasma levels of N-terminal pro-brain natriuretic peptide (NT-proBNP). Regarding fasting plasma parameters, the N178T variant was associated with a lower concentration of glucose. Accordingly, P2Y4 KO mice had significantly improved glucose tolerance and insulin sensitivity compared with their WT littermate controls. The improvement of insulin sensitivity resulting from lack of the P2Y4 receptor was no longer observed in the absence of adiponectin. The present study identifies a frequent loss-of-function P2Y4 variant associated with less severe coronary artery atherosclerosis and lower fasting plasma glucose in coronary patients. The role of the P2Y4 receptor in glucose homeostasis was confirmed in mouse. P2Y4 antagonists could thus have therapeutic applications in the treatment of myocardial infarction and type 2 diabetes.